IFLA tyrimas „Funkciniai reikalavimai bibliografiniam įrašui" ir jo reikšmė valstybinės bibliografijos tarnyboms ir kataloguotojams - Janonis, Osvaldas (Knygotyra, 2002)
The introduction to the article gives an account of the international co-operation in the sphere of cataloguing since 1954. AI present one of the most important problems is the price of the cataloguing process. The creation of a full bibliographic record by the national bibliographic services is an expensive activity. Therefore the idea of its simplification came into being. The attention was focused on the functionality of a bibliographic record. IFLA has organised a special research of this problem. The main goal of the article is to analyse the organisation and the results of the study from the point of view of its significance for national bibliographic services, cataloguers, and teachers of cataloguing disciplines. The author has arrived to the following conclusions: the model provided by the study demonstrates that a bibliographic description is a complex system; the model includes the variety of works and information carriers; it embraces the variety of needs of a wide range of information users; the results will enhance theoretisation of cataloguing science and corresponding disciplines; the results of the study are significant for bibliographic practice; they will influence the preparation and revision of the national cataloguing rules and further development of the international standards of bibliographic description; the study is interesting from the point of view of enriching the functional possibilities and shortening the time of bibliographic search; the implementation of the results will mean the improvement of the quality of a bibliographic description and will ensure the provision of full data. The Centre of National Bibliography and Book Science has a task to analyse how their bibliographic descriptions fit with the basic level of national bibliographic description and to take the results of the study into account while preparing the national rules of cataloguing. The author thinks that the experience of the Royal School of Library and lnformation Studies in Denmark accumulated during research process for the IFLA study has to be taken into account by Vilnius and Klaipėda universities that educate librarians in Lithuania.